2019
DOI: 10.1192/bjp.2018.298
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of early intervention in psychosis: systematic review

Abstract: BackgroundEarly intervention in psychosis (EIP) has been developed as an approach to improve the prognosis of people with psychotic disorders and it has been claimed to be a more efficient model of care. However, the evidence is not definitive and doubts have spread regard to the economic outcomes of EIP services amid the usually restricted mental health budget.AimsWe aimed to review the cost-effectiveness evidence of EIP services worldwide.MethodWe systematically reviewed the economic literature about EIP fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 42 publications
4
61
0
1
Order By: Relevance
“…Using analytical models to compare EIP with care as usual for people with first‐episode psychosis, results showed that EIP could save around £2,000 per person over 3 years because of improved employment and education outcomes, and approximately £1,000 per person over 4 years because of reduced suicide rates. More recently, a systematic review of 16 studies found consistent evidence of cost‐effectiveness of EIP in people with first‐episode psychosis or clinical high risk for psychosis, compared with care as usual.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Using analytical models to compare EIP with care as usual for people with first‐episode psychosis, results showed that EIP could save around £2,000 per person over 3 years because of improved employment and education outcomes, and approximately £1,000 per person over 4 years because of reduced suicide rates. More recently, a systematic review of 16 studies found consistent evidence of cost‐effectiveness of EIP in people with first‐episode psychosis or clinical high risk for psychosis, compared with care as usual.…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…As noted in another systematic review on EIP, indicators that are more valued and relevant to people, health and care systems, and policy makers – such as social recovery, budget impact analyses, and equity measurements – are beginning to be included in the research agenda, although issues such as non‐cashable savings and silo mismatches would be some of the foreseeable challenges with these outcome measures (see below).…”
Section: Current Economic Evidence and Key Events In Mental Health Carementioning
confidence: 99%
“…This comes at a pivotal time for Irish mental health services because we are now on the cusp of joining this international movement by rolling out our own EIP services nationally. EIP services have a proven track record of raising the standard of care and treatment, improving outcomes, reducing suffering, limiting the burden of care and reducing costs (Fusar-Poli et al 2017;Correll et al 2018;Aceituno et al 2019). EIP has injected hope into a previously pessimistic view of psychosis (Goldner-Vukov et al 2007;McGorry, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Investment will need to be flexible to accommodate the wide variation in demand between rural, urban and metropolitan areas (Kelly et al 2010;Kirkbride, 2015). Although these EIP services are likely to bring with them considerable downstream cost savings (McCrone et al 2008;Park et al 2016;Aceituno et al 2019), these are unlikely to be seen in the first couple of years of operation.…”
Section: The Introduction Of Eip Services In Irelandmentioning
confidence: 99%
“…The most consistent evidence is from trials of specialist EIP care versus treatment as usual, which shows better short‐to‐medium clinical and functional outcomes for those receiving EIP care, as well as cost‐effectiveness of EIP, while the evidence of specific effective CHR/UHR interventions to prevent the emergence of psychosis remains unclear.…”
mentioning
confidence: 99%